MILENIAL DAN UANG : APA YANG MEMPENGARUHI KEUANGAN MEREKA? APA YANG MEMPENGARUHI KEUANGAN MEREKA? - wargadalam, winanda wahana; Wardani, Dian Puspa (Pusat P2M Politeknik Negeri Batam, 2024)
The proposed research is based on the theory of planned behavior and social learning theory which aims to examine the effect of financial knowledge, financial attitudes, self-control, and lifestyle on financial management behavior in the millennial generation in Batam City. This research is a quantitative descriptive research and the instrument used is by using a questionnaire via google form. The population in this study were active students at the Batam State Polytechnic majoring in Business Management, Accounting and Managerial Accounting study programs, for the 2018/2019 class of employees and regular classes. Students were chosen as the population in this study because students are represented as millennials, which is the age at which they are given the power to manage their own finances. So that requires them to start being independent in managing finances and start making responsible decisions. Samples were obtained using the Slovin formula as many as 133 student samples. Then the data obtained was processed using IBM SPSS 25 software. The analytical tools used were validity and reliability tests, classical assumption tests, multiple linear regression and hypothesis testing in the form of t-test, f-test and coefficient of determination. The results of this study indicate that the variables of financial knowledge, financial attitudes, self-control, and lifestyle have a positive and significant effect on financial management behavior.